Molecules Present in Plant Essential Oils for Prevention and Treatment of Colorectal Cancer (CRC) - Petrocelli, Giovannamaria (Molecules, 2021)
Essential oils (EOs) are a complex mixture of hydrophobic and volatile compounds synthesized from aromatic plants, commonly present in the human diet. In recent years, many in vitro studies have suggested possible anticancer properties of single EO compounds, on colorectal cancer (CRC) cells. However, the majority of these studies did not compare the effects of these compounds on normal and cancer colon cells. By using NCM-460, a normal human mucosal epithelial cell line, Caco-2, a human colon epithelial adenocarcinoma cell line, and SW-620, colon cancer cells derived from lymph node metastatic site, we identified cinnamaldehyde, derived from cinnamon EO and eugenol, derived from bud clove EO, as compounds with a specific anticancer action selectively targeting the transformed colonic cells. Both cinnamaldehyde (75 µM) and eugenol (800 µM), after 72 h of treatment, were capable to induce apoptosis, necrosis and a cell cycle slowdown in Caco-2 and in SW-620, but not in NCM-460 cells. If associated with a targeted delivery to the colon, these two compounds could prove effective in the prevention or treatment of CRC.